KEHATI-HATIAN NOTARIS DALAM MENJALANKAN JABATANNYA TERKAIT PEMBERIAN SALINAN/GROSSE/KUTIPAN AKTA - lewis irfan (JOURNAL EQUITABLE, 2021)
Notary is a position was born because of the needs of the community. In development in a written regulation or unwritten policy from people who want the intervention of a notary as an absolute requirement, the choice of the authority of a notary, an official other than a notary. Obligation to keep confidential belief which is the will conveyed by the presenter (-s) is born automatically because of the position of a notary. Notary have an obligation to make Original of the Deed and keep them as a protocol, a notary to people who have a direct interest in the Original of the Deed, heirs, or the person obtaining the right is given Original Copy of a Deed, grosse, or excerpt of a deed. Notary who faced with the difficulty of determining whether one can obtain Original Copy of a Deed/grosse/excerpt deed in order to ask the person concerned to ask for a written power of attorney or a court order to issue and provide Original Copy of a Deed/grosse/ excerpt of a deed to the party requesting the notary. Sanctions given for not maintaining confidentiality by a notary is criminal, civil, imprisonment and fines, administration, and code of ethics.